Faktor-faktor yang mempengaruhi Penerimaan Nelayan di Desa Kalirejo Kecamatan Kraton Kabupaten Pasuruan - Paradigma Muhammad; Elys Fauziyah (Department of Agribusiness, University of Trunojoyo Madura, 2022)
This study aims to describe and analyze the factors that influence the income of fishermen in Kalirejo Village, Kraton District, Pasuruan Regency. This study uses multiple linear regression analysis with 42 fishermen as respondents. The results of the study show that together the independent variables (age, working hours once at sea, experience, capital, and dummy tools used) have a significant effect on the dependent variable, namely income. Partially or individually, all independent variables (age, working hours once fishing, experience, capital, and dummy tools used) have a significant effect on the income variable.